Expressed fusion gene landscape and its impact in multiple myeloma. Issue 1 (December 2017) - Cleynen, A.; Szalat, R.; Kemal Samur, M.; Robiou du Pont, S.; Buisson, L.; Boyle, E.; Chretien, M.; Anderson, K.; Minvielle, S.; Moreau, P.; Attal, M.; Parmigiani, G.; et al.
Abstract Multiple myeloma is a plasma cell malignancy characterized by recurrentIgH translocations and well described genomic heterogeneity. Although transcriptome profiles in multiple myeloma has been described, landscape of expressed fusion genes and their clinical impact remains unknown. To provide a comprehensive and detailed fusion gene cartography and suggest new mechanisms of tumorigenesis in multiple myeloma, we performed RNA sequencing in a cohort of 255 newly diagnosed and homogeneously treated multiple myeloma patients with long follow-up. Here, we report that patients have on average 5.5 expressed fusion genes. Kappa and lambda light chains andIgH genes are main partners in a third of all fusion genes. We also identify recurrent fusion genes that significantly impact both progression-free and overall survival and may act as drivers of the disease. Lastly, we find a correlation between the number of fusions, the age of patients and the clinical outcome, strongly suggesting that genomic instability drives prognosis of the disease. Multiple myeloma is a malignancy of plasma cells in the blood. Here, the authors establish the landscape of fusion genes within this disease, identifying novel recurrent fusion genes that impact survival and may drive disease progression.